PENGARUH DER, ROE, ROA, NPM, DAN EPS TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR - Yuliana, Rini Tri Hastuti (Jurnal Paradigma Akuntansi, 2020)
The purpose of this study was to analyze the effect of debt to equity ratio, return on equity, return on asset, net profit margin, earning per share on stock prices on manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Samples that can be found in this study were 63 companies using purposive sampling techniques. The technique for processing data uses multiple regression analysis using Eviews application version 10.0 and Microsoft Excel 2010. Simultaneously debt to equity ratio, return on equity, return on asset, net profit margin, earning per share together there is an influence on stock prices. Partially the results of this study indicate that return on asset and earning per share have a positive influence on stock prices. Return on equity and net profit margin have a negative effect on stock prices while debt to equity ratio has no positive effect on stock prices.